PENERAPAN KEMAHIRAN EMPLOYABILITY DALAM PENGAJARAN DAN PEMBELAJARAN DI KOLEJ KOMUNITI DI NEGERI JOHOR - Yusof, Yusmarwati; Mohd Alwi, Noor Shahira Amiza; Roddin, Rohayu; Awang, Halizah (Online Journal for TVET Practitioners, 2018)
Employability skills are the skills required by students to prepare them for the employment. However, there is limited study conducted in the training institution such as community colleges. Therefore, this study is conducted to identify the application of the 'employability' skills that frequently implemented by lecturers at community colleges in Johor. This study is also to understand the skill that is mastered the most by the students, and the problems faced by the lecturers in inculcating this skill. The skills elements studied included the seven key elements of employability skills which are; communication, leadership, teamwork, problem solving, ethical and professional and business skills. The study is a survey study using a questionnaire as the main instrument. Questionnaire was distributed to 140 students and 44 lecturers from three community colleges in Johor. The data were collected and analyzed using the Statistical Packages for Social Science (SPSS) version 21.0 to obtain mean score and standard deviation. The findings indicated that the frequent skill employed by lecturers in teaching and learning process is bussiness skill. The most mastered skill by students is also the business skill. Among challenges that need to be faced by lectures are lack of computer skills as well as lacking skills in using technology. It is important for lecturers to emphasize employability skills equally in their teaching. Whereas, students need to work to master the employability skill as a platform to prepare them for the workplace. This study is hoped to help lecturers and students prepare to enhance their employability skills.